(untitled) (International Seven Journal of Health Research, 2023)
Introduction: The practice of physical activity in the elderly is associated with a life with greater self-esteem and self-confidence, especially when this activity is carried out in a group, with this, this elderly to have a healthier life, promoting greater functional independence, improvement of the social aspect and with greater autonomy in decision making as they age. Objective: to observe the level of self-esteem in elderly people who practice physical activity belonging to the Alegria de Viver Group, in the Service of Coexistence and Strengthening of Bonds for the Elderly, located in the municipality of Montanha - ES, Brazil. Methodology: This is a quantitative, exploratory and descriptive research, which was applied in the Service of Coexistence and Strengthening of Bonds for the Elderly. For data collection, a questionnaire with 10 questions with 4 alternatives each was applied to 40 elderly people aged between 56 and 97 years who are part of the Alegria de Viver Group, on May 4, 5 and 8, 2023. Results: 100% of the elderly reached a score above 15, presenting a high level of self-esteem and self-image. Conclusion: It was concluded that the regular practice of physical exercises performed by the elderly can have a positive impact on their self-esteem. Physical activity provides physical and mental well-being, especially in raising their self-esteem and confidence for a more active life.